2019
DOI: 10.1021/acsomega.8b03665
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Microwave-Assisted Synthesis of the 2D-BiOCl/2D-g-C3N4 Heterostructure for the Degradation of Amine-Based Pharmaceuticals under Solar Light Illumination

Abstract: Designing efficient 2D-bismuth oxychloride (BiOCl)/2D-g-C 3 N 4 heterojunction photocatalysts by the microwave-assisted method was studied in this work using different amounts of BiOCl plates coupled with g-C 3 N 4 nanosheets. The effects of coupling the 2D structure of g-C 3 N 4 with the 2D structure of BiOCl were systematically examined by scanning electron microscopy (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Common drugs examined in photocatalytic studies include tetracycline (TC), [117] oxytetracycline, [118] ciprofloxacin (CIP), [48] ibuprofen (IBF), [69] levofloxacin, [119] naproxen, [120] acetaminophen, [121] carbamazepine, [122] sulfamethazine, [123] and nizatidine. [124] Table 6 lists the testing conditions and TC degradation activity of some g-C 3 N 4 -based Reproduced with permission. [116] Copyright 2018, Elsevier.…”
Section: Drug Degradationmentioning
confidence: 99%
“…Common drugs examined in photocatalytic studies include tetracycline (TC), [117] oxytetracycline, [118] ciprofloxacin (CIP), [48] ibuprofen (IBF), [69] levofloxacin, [119] naproxen, [120] acetaminophen, [121] carbamazepine, [122] sulfamethazine, [123] and nizatidine. [124] Table 6 lists the testing conditions and TC degradation activity of some g-C 3 N 4 -based Reproduced with permission. [116] Copyright 2018, Elsevier.…”
Section: Drug Degradationmentioning
confidence: 99%
“…The influence of shape on the photocatalytic activity of BiOCl for the degradation of toxic bisphenol A was tested for microplates and microflowers, and it was confirmed that the higher adsorption capacity and presence of more active sites in the microflowers enhanced their photocatalytic activity 10 . Other BiOCl-based nanostructures such as BiOCl/Bi 2 S 3 , BiOCl/(BiO) 2 CO 3 , and BiOCl/g-C 3 N 4 heterostructures are also good photocatalysts [11][12][13] .…”
Section: Broadband Dielectric Spectroscopy For Monitoring Temperaturementioning
confidence: 99%
“…In particular, bismuth oxychloride (BiOCl) has attracted significant interest due to its unique crystallographic structure, which can establish an internal electric field for interlayer charge transfer [11,12]. However, the catalytic performance of BiOCl is restricted by the poor photogenerated charge separation ability and inactiveness of visible light utilization, which reduces the overall efficiency [13,14]. Therefore, various strategies, such as surface modification, defect engineering, morphology control, and heterojunction construction, have been widely adopted to tailor the photocatalytic activity of BiOCl [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The construction of heterojunction composites has been studied in order to enhance the light absorption, the charge separation efficiency, and the lifetime of carriers [10,17]. Up to now, various BiOCl-based composites have been developed on the basis of this fundamental mechanism, such as BiOCl/g-C 3 N 4 [14], BiOCl/Bi 24 O 31 Cl 10 [18], and NiO/BiOCl [19]. It is well known that the heterojunction effect is established by an electronic coupling effect produced from the interfacial interactions of two components to enhance light-responsive capability and expedite interfacial charge carrier mobility [10,20].…”
Section: Introductionmentioning
confidence: 99%